Rekonstruksi Makna dan Nilai Identitas Sosial Jawara Banten Untuk Pendidikan Karakter - Hanif, Ehza Alifan; Nurbayani K., Siti; Komariah, Siti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the phenomenon of Jawara Banten identity formation through a phenomenological approach focused on the lived experience and subjective meanings of its cultural inheritors. The jawara, who are negatively stigmatized by society, actually possess noble values, such as religiosity, courage, justice and solidarity, trustworthiness and honesty, as well as authority and well-being. These values can be emulated and integrated into lessons and extracurricular activities to strengthen character education among students. Thus, problems of moral degradation and student delinquency, such as drug abuse, brawls, and violence, can be addressed through the understanding and internalization of these noble values as a form of local wisdom that serves as a source for strengthening character education. Using the framework of Social Identity Theory by Henri Tajfel and John C. Turner, this article examines how the true jawara identity is constructed. The research approach is qualitative, employing a phenomenological method through in-depth interviews and a literature review. The results show that the formation of a positive jawara identity occurs through three psychosocial processes: (1) Social categorization, which firmly distinguishes the in-group of "true jawara" from the out-group of "thugs" or "henchmen"; (2) Social identification, where the jawara internalize noble values—namely being religious, courageous, trustworthy, honest, just, and authoritative—as the prototype of their identity ; and (3) Social comparison, which is a conscious effort to build a positive and respected image of the jawara in the eyes of society. This process of reconstructing identity meaning offers a rich and authentic model of local wisdom for strengthening character education. The noble values of Jawara Banten can be integrated into school subjects such as History, Social Studies, and Civics. Furthermore, the philosophy and heroism of Jawara Banten can serve as a source for reinforcing a character education that is rooted in national culture.